Genome-Wide Analysis of Gene Regulatory Networks of the FVE-HDA6-FLD Complex in Arabidopsis - Yu, Chun-Wei; Chang, Kao-Yuan; Wu, Keqiang (Frontiers in Plant Science, 2016)
FVE/MSI4 is a homolog of the mammalian RbAp48 protein. We found that FVE regulates flowering time by repressing FLC through decreasing histone H3K4 trimethylation and H3 acetylation. Furthermore, FVE interacts with the histone deacetylase HDA6 and the histone demethylase FLD, suggesting that these proteins may form a protein complex to regulate flowering time. To further investigate the function of the FVE-FLD-HDA6 complex, we compared the gene expression profiles of fve, fld and hda6 mutant plants by using RNA-seq analysis. Among the mis-regulated genes found in fve plants, 51.8% and 36.5% of them were also mis-regulated in fld and hda6 plants, respectively. These results suggested that FVE, HDA6, and FLD may regulate the gene expression in the same developmental processes in Arabidopsis. 383 genes were found to be co-regulated by FVE, HDA6, and FLD. Gene Ontology (GO) analysis reveals that 15.6% of these co-regulated genes are involved in transcription, 8.2% in RNA metabolic process, 7.7% in response to abiotic stress, and 6.3 % in hormone stimulus, indicating that HDA6, FVE, and FLD co-regulate the gene expression in multiple development processes and pathways.